علاقة النمط القيادي حسب نظرية هيرسي وبلانشارد بالالتزام التنظيمي لدى موظفي جامعة عمار ثليجي الأغواط - عبد العليم الحاج أحمد; حموش يسين; محمد بوفاتح (My University, 2021)
This study aimed to find out what the leadership style has to do with organizational commitment, according to Hirsi and Blanchard's theory of staff at Ammar Thligi University in Ghouta. In this study, I relied on two data collection tools, the Regulatory Compliance Scale Questionnaire, which contains 19 items. The tool describes the effectiveness and adaptation of Hirsi and Blanchard in order to determine the leadership pattern followed, and the tool includes 12 positions reflecting the levels of maturity of subordinates, and this study was applied to a sample of 40 employees at The University of Ammar Theligi Balagoat. The study reached the following conclusions:  The prevailing leadership pattern is that of participation.  The level of organizational commitment of the staff of Ammar Thligi University in the air is average.  There are statistically significant differences between leadership patterns in favour of the participating leadership pattern.  There are no differences in regulatory commitment attributable to seniority, according to Hirsi and Blanchard theory.  There are differences between high and low regulatory commitmen